Comparison of Recurrence Patterns and Salvage Treatments After Definitive Radiotherapy for cT1a and cT1bN0M0 Esophageal Cancer - Kawamoto, Terufumi; Shikama, Naoto; Mine, Shinji; Sasai, Keisuke (Frontiers in Oncology, 2022)
Background: Definitive radiotherapy (RT) for Stage I esophageal cancer was reported to result in noninferior overall survival (OS) compared with surgery. However, there are few detailed reports of recurrence patterns and subsequent salvage treatments. This study aimed to compare recurrence patterns and subsequent salvage treatments after definitive RT or chemoradiotherapy (CRT) between cT1a and cT1bN0M0 esophageal cancer (EC). Methods: Patients with cT1a or cT1bN0M0 esophageal squamous cell carcinoma were included. Patients received definitive RT or CRT. Survival outcomes, recurrence patterns, and salvage treatments were evaluated. Results: In total, 40 patients with EC receiving RT or CRT were divided into two groups for evaluation: the cT1a group (20 patients) and the cT1b group (20 patients). The 3-year OS rates were 83% and 65% (p = 0.06) and the 3-year progression-free survival rates were 68% and 44% (p = 0.15) in the cT1a and cT1b groups, respectively. Among those in the cT1a group, six had local recurrence and two had metachronous recurrence. Seven patients underwent salvage endoscopic submucosal dissection, and one patient received argon plasma coagulation treatment. Among those in the cT1b group, six had local recurrence, one had regional recurrence, and one had both. Among them, one underwent salvage endoscopic submucosal dissection, one received photodynamic therapy, three underwent surgery, one received RT, and two received best supportive care. Compared with the cT1b group, the cT1a group had a higher proportion of patients who underwent endoscopic treatments (p = 0.007). After the endoscopic treatments, no recurrences were observed in both groups. Conclusions: Regional recurrence and distant metastasis were not observed in the cT1a group. A higher proportion of patients in the cT1a group were able to receive salvage endoscopic treatments and their OS tended to be favorable.